Internet-Based Interventions for the Prevention and Treatment of Depression in People Living in Developing Countries: A Systematic Review - Martinez-Diaz, P (Elsevier B.V., 2018)
Background: Internet-based interventions for depression may be a valuable resource to reduce the treatment gap for those living in developing countries. However, evidence comes mainly from developed countries. This systematic review summarized the evidence on preventive or therapeutic Internet-based interventions for depression for people who reside in developing countries. Methods: CINAHL, EMBASE, PubMed, SciELO Citation Indexes, the Journal of Medical Internet Research, and the Telemedicine and e-Health journal, were searched up to June 2017, to identify feasibility or effectiveness studies of preventive or therapeutic Internet-based interventions for depression, with or without human support. Studies included subjects residing in developing countries, and were published in English or Spanish. Study protocols were included. Risk of bias and/or quality of the reporting of the studies included was assessed. Results: Five feasibility studies, aimed at the prevention of depression, and a study protocol were included in this systematic review. Reports came mostly from the Americas (n = 4). Internet-based interventions aimed at the prevention of depression presented low levels of human support, were useful and acceptable to their users, and require further design refinements to improve their use and retention. Limitations: No gray literature was searched or included in this systematic review. Searches were limited to English and Spanish languages. Discussions: Internet-based interventions aimed at the prevention of depression in people who reside in developing countries are in an early phase of development, limiting the generalizability of the results. Future studies must employ persuasive designs to improve user retention, incorporating larger samples and a control group to conclusively determine feasibility. © 2018 Elsevier B.V.